Research on the new trend of sustainable development of rural tourism in Xi’an in the post pandemic period - Wan, Bo; Bi, Chuanchen (Technium Social Sciences Journal, 2022)
In 2019, the COVID-19 broke out in Wuhan, China, and then spread to the whole country. In April of the following year, China announced that it had entered the Normalized Management stage for the COVID-19. This article describes the current situation of rural tourism in Xi’an by introducing the rise and development of rural tourism in Xi’an, as well as the impact of the COVID-19 on rural tourism in Xi’an. According to the current situation of rural tourism in Xi’an, the SWOT analysis has been introduced to find out the advantages, disadvantages, opportunities and challenges of rural tourism in Xi’an. Leverage Effect (advantage & opportunity), Inhibition (disadvantage & opportunity), Vulnerability. (advantages & threats) and Problems (disadvantages & threats) have been analyzed to obtain a corresponding strategic plan suitable for the sustainable development of rural tourism in Xi’an.